Secondary Productivity of Crambidae Family in Cigambreng River, Tapos Village, Bogor: Produktivitas Sekunder Famili Crambidae di Sungai Cigambreng, Desa Tapos, Bogor - Nurcahyanto, Arif; Pulungan, Ahyar; Abdillah, Didit; Afif, Muhammad Irfan; Panggabean, Grin Tommy; Kawirian, Rizky Regina; Rahman, Chichilia Qaila Azzahra; Krisanti, Majariana (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
Secondary productivity is the formation of biomass of heterotrophic organisms in units of time including biomass that is lost in a certain time unit. The Crambidae family is an insect that has aquatic larvae and will become an air insect after the larval phase. This species has the potential to become a pest for agriculture. The study was conducted in October 2019 for one month. The Crambidae family species found consists of two species, Petrophila sp. and Elophila sp. The abundance of Crambidae during the study ranged from 100 ind/m2 to 422 ind/m2. Secondary productivity was analyzed by the size frequency method. The secondary productivity of the Crambidae family in Cigambreng river waters for one month was 47.7915 g/m2/month, the biomass formed was 14.9669 g/m2 and the P/B ratio was 3.1931.